Nonlinearities and Workers' Heterogeneity in Unemployment Dynamics - Stéphane Adjemian; Frédéric Karamé; François Langot (Institute of Labor Economics (IZA), 2021)
This study demonstrates that nonlinearities, coupled with worker heterogeneity, make it possible to reconcile the Diamond–Mortensen–Pissarides model with the labor market dynamics observed in the United States. Nonlinearities, induced by firings and downward real wage rigidities, magnify adjustments in quantities, whereas heterogeneity concentrates them on the low-paid workers' submarkets. The model fits the job finding, job separation, and unemployment rates well. It also explains the Beveridge curve's dynamics and the cyclicality of the involuntary component of separations. The estimated dynamics of the aggregate shock that allows generating the US labor market fluctuations has a correlation with unemployment that changes of sign during the 80s. We also show that the differences in adjustment between submarkets predicted by the model are consistent with the data of job flows by educational attainment.
Keywords: C51; E24; E32; 330; search and matching; unemployment dynamics; nonlinearities; particle filter; maximum likelihood estimation